Functional plasticity in lateral hypothalamus and its prediction of cognitive impairment in patients with diffuse axonal injury: evidence from a resting-state functional connectivity study. Issue 7 (5th May 2021) - Wang, Yao; Zhou, Fuqing; Li, Yan; Li, Jian; Kuang, Hongmei; Chen, Qi; Hong, Tao; Gong, Honghan
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Diffuse axonal injury (DAI) is a common pathological process after traumatic brain injury, which may cause survivors severe functional disorders, including cognitive impairment and physical disability. Recent literature indicated lateral hypothalamus and medial hypothalamus damage during DAI. Thus, we aim to investigate whether there is imaging evidence of hypothalamic injury in patients with DAI and its clinical association. Methods: Twenty-four patients with diagnosed DAI and 26 age and sex-matched healthy controls underwent resting-state functional MRI. We assessed the lateral hypothalamus and medial hypothalamus functional connectivity with seed-based analysis in DAI. Furthermore, a partial correlation was used to measure its clinical association. The prediction of the severity of DAI from the altered lateral hypothalamus and medial hypothalamus connectivity was conducted using a general linear model. Results: Compared with healthy control, the DAI group showed significantly decreased lateral hypothalamus functional connectivity with the basal ganglia and cingulate gyrus, which was positively correlated with mini-mental state examination scores (Bonferroni correction at P < 0.0125). Importantly, this disrupted functional connectivity can be used to predict the patients' cognitive state reliably ( P = 0.006; P = 0.009, respectively) in DAI. Moreover, we also observed increased connectivity of medial hypothalamus with the superior temporal gyrus and the regions around the operculum. Furthermore, there was a trend of negative correlation between the medial hypothalamus functional connectivity changes to the right superior temporal gyrus and the disability rating scale scores in the DAI group. Conclusion: Our results suggest that there are alterations of medial hypothalamus and lateral hypothalamus connectivity in DAI and further understand its clinical symptoms, including related cognitive impairment.